Flexural strengthening of reinforced concrete cantilever beams having insufficient splice length - Moataz Badawi; Alireza Bahrami; Mohamed Ghalla; Mohamed Emara; Ehab A. Mlybari; Galal Elsamak (Results in Engineering)
Structural systems often undergo changes due to variations in the usage, the loading conditions, or the presence of defects in their elements. The problem can be exacerbated when there is insufficient overlap between reinforcing bars in critical moment zones. This article investigates the behavior of reinforced concrete cantilever beams exhibiting insufficient overlap between bars that used as main reinforcing steel bars in the negative moment zone. Various strengthening techniques were employed in order to improve these defected cantilever beams. Eleven beams underwent flexural testing until reaching failure. The experimental parameters encompassed the strengthening scenarios and the bonded length. Three strategies were used: the application of stainless-steel plates (SSPs) as externally bonded reinforcement, near surface mounted (NSM) reinforcement in which additional deformed steel bars were bonded utilizing engineering cementitious composites, and externally pre-stressing technique. The anchorage length was examined at 40, 50, and 60 times the internal bar diameter. It was noted that the most substantial improvement achieved with the NSM method, followed by the externally pre-stressing method. It is worth mentioning that most of the beams failed in a flexural manner, with partial debonding occurring in beams strengthened using external strengthening. Moreover, this article includes the development of a numerical model employing the finite element method to replicate the response observed from the experimentally tested beams. The accuracy of the model was confirmed through the comparison of its outcomes with the experimental data, demonstrating an acceptable level of accuracy with deviations of less than 4.4 %. This successful numerical investigation was also used to conduct a parametric study. From this study it is evident that the effect of debonding on SSPs can be reduced by adding steel anchors at the ends of these plates. Finally, an analytical method was proposed to calculate the ultimate load capacity of strengthened reinforced concrete beams.